2017
DOI: 10.1063/1.4971652
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic simulations of microjetting from shock-loaded grooves

Abstract: Abstract. The interaction of a shock wave with a free surface which has geometrical defects, such as cavities or grooves, may lead to the ejection of micrometric debris at velocities of km/s. This process can be involved in many applications, like pyrotechnics or industrial safety. Recent laser shock experiments reported elsewhere in this conference have provided some insight into jet formation as well as jet tip velocities for various groove angles and shock pressures. Here, we present hydrodynamic simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…[6,7] Roland et al used the smoothed particle hydrodynamics (SPH) to study the size distribution of fragments in copper samples loaded by laser shock, and at the same time quantified the effect of distance between particles and smooth length on the results. [15] Dyachkov et al compared the results of the SPH simulation with the experimental results, showing that the size of the surface defects has a greater influence on the jet head velocity. [16] Soulard et al investigated the surface failure characteristics of metallic copper under triangular wave loading by MD simulation, mainly analyzing the surface characteristics of impact melting and unloading melting, and calculated the curves required for thermodynamic analysis such as shock Hugoniot line and shock melting line.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Roland et al used the smoothed particle hydrodynamics (SPH) to study the size distribution of fragments in copper samples loaded by laser shock, and at the same time quantified the effect of distance between particles and smooth length on the results. [15] Dyachkov et al compared the results of the SPH simulation with the experimental results, showing that the size of the surface defects has a greater influence on the jet head velocity. [16] Soulard et al investigated the surface failure characteristics of metallic copper under triangular wave loading by MD simulation, mainly analyzing the surface characteristics of impact melting and unloading melting, and calculated the curves required for thermodynamic analysis such as shock Hugoniot line and shock melting line.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, Piriz et al [23] proposed an analytical model based on the linear Richtmyer-Meshkov instability (RMI) in solids under the conditions of high-energy-density, and showed that plasticity determined the maximum perturbation amplitude and provides simple scaling laws. Besides, molecular dynamics (MD) [1,12,24,25], Eulerian [14,26,27], and smoothed particle hydrodynamics (SPH) [28][29][30] methods have all been used to simulate the microjet formation. Dimonte et al [31] described a simple algebraic model for the microjet based on the hydrodynamics and MD simulations of the RMI.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of viscosity to reduce the growth rate of Richtmyer-Meshkov instabilities (RMI) in fluids has been studied for some time [1][2][3][4][5]. The sensitivity of RMI to strength in solids, the analog of viscosity, has received explicit attention more recently [6][7][8][9][10][11][12] with increasing attention also in regard to ejecta [13][14][15][16]. Since the proposal about a decade ago to use RMI to evaluate strength [17,18], several experimental efforts to use this capability have been reported [19][20][21][22][23][24][25][26][27][28][29], although in many cases the experiments serve as validation experiments for strength models rather than providing quantitative estimates of strength.…”
Section: Introductionmentioning
confidence: 99%